PENANAMAN NILAI ETIKA HIDUP KRISTEN MELALUI LITERASI DIGITAL - Nurlia Langi Marempang; Ice’ Pombiu’ Bedyona, Norva Palimbong, Firdayanti, Since Lorenata (ADISAM PUBLISHER, 2025)
The purpose of the study is to find concepts that can be applied by Christian religious leaders in instilling the values and meanings of Christian life ethics through the use of digital literacy, especially in the 21st century surrounded by the age of digital technology. In this study the authors use qualitative methods with a descriptive analysis approach. Qualitative methods are applied in the form of literature that takes sources from trusted literature such as books, articles and internet sources that can be recognized by the truth. While descriptive analysis is carried out with a view to developing the author's intentions in accordance with the real reality in the field to be developed in a scientific work. There are several theories used by the author, such as the theory developed by Leny Muniroh about the model that can be applied by Christian religious leaders in developing digital technology as a form of literacy in building Christian ethics. The second theory by Basoeky's superior to the use of digital technology by Christians to build togetherness. The expected result of this study is that the ethics of Christian life can not only be done by the government but also by Christian religious leaders through digital literacy technology education to develop, apply and disseminate the teachings of Christianity in accordance with God's will and Bible teachings